11β-hydroxylase deficiency disorders - Mai, Nguyễn Thị Phương; Hải, Nông Văn; Hoàng, Nguyễn Huy (Vietnam Journal of Biotechnology, 2018)
Congenital adrenal hyperplasia (CAH) is a family of autosomal recessive disorders which is characterized by a deficiency of one of the enzymes involved in the synthesis of cortisol from cholesterol by the adrenal cortex. 90% CAH patients respond to 21-hydroxylase deficiency. Less causes include deficiencies of 11β-hydroxylase (11-OH), 17- hydroxylase (17-OH), 3β- hydroxysteroid dehydrogenase (3β- HSD), 20/22 Desmolase etc.. Because of the blocked enzymatic steps, cortisol precursors usually presents with signs of androgen excess which are secreted and cause in masculinization of female external genital, hyponatremia, hyperkalemia and hypovolemia in the classic form due to 21-hydroxylase deficiency. By the early 1950s, it was recognized that in some CAH patients with hypertension develops. This symptom responds to glucorticoid replacement. Most of these patients have an 11β-hydroxylase deficiency. CAH cases arise from 11β-hydroxylase impaired is the second most common form. Mutations in the CYP11B1 gene are the cause of 11β-hydroxylase deficiency. The incident of 11β-hydroxylase deficiency is about 5% to 8% of cases with CAH, in approximately 1/100,000 live birth. Mutations have been detected from different ethnic backgrounds with the highest incidence in group of Morrocan Jews. This article reviews function of enzyme 11β-hydroxylase in cortisol synthesis of andrenal cortex, structure of CYP11B1 gene, diagnosis and treatment of 11β-hydroxylase deficiency and summarised of researching in Wordwild and in Vietnam. Genetic characterization of CYP11B1 genotype has improved our understanding of the phenotype differences in patients. This could be serve as a the basis for genetic counseling and prenatal diagnosis in the future